Standardization of Raven's standard progressive matrices for secondary school African pupils in the Grahamstown region - Vass, Vasili Arthur (Rhodes University, Faculty of Humanities, Department of Psychology, 1992)
Arising out of a need, expressed by Clinical Psychologists in the Grahamstown region, for the fair assessment of secondary School African pupils, norms for the Raven's Standard Progressive Matrices (SPM) were established. Two methods of presentation were used, the first using the original instructions of John Raven translated into the students' first language of Xhosa, hence-forth referred to as the Alternate sample. The second method of presenting the instructions was adapted, to include the use of visual aids and active participation in the instruction phase of the test, hence-forth referred to as the Normative sample. In addition to the establishment of norms, the two methods of test presentation were investigated to see if the method of presentation had an effect on the results of the Raven's SPM. The population was drawn from the three African Secondary Schools in the Grahamstown municipality. The total population consisted of 3 232 students. Classes were randomly sampled across the three schools, with the average age of the Normative sample being 19.3 years. The sample consisted of 812 pupils, 711 in the Normative sample and 101 in the Alternate Sample. The following results and conclusions arose from the study: 1) Norms generated were considerably lower than previously established norms in similar studies. 2) t-Test results indicated that the method of test presentation on the Raven's SPM is important when assessing students that may be regarded as 'disadvantaged'. 3) Respondents scored significantly higher when the method of presenting the instructions ensured a greater understanding of the task demanded of the respondents. 4) The analyses of covariance indicate that male subjects score significantly higher than female subjects, and that there is a significant difference between the ages and educational standard, on the scores of the Raven's SPM. 5) The differences found contradict previous findings using the test, and question the cultural fairness of the test.
Keywords: Black people -- Education -- South Africa; Intelligence tests -- South Africa; Educational tests and measurements -- South Africa; Cognition and culture; Raven's Progressive Matrices